Tiktok as an Alternative Learning Media for the Z Generation: Phenomenology Research - Nababan, Kartyka; Harahap, Putri Bintang Pratiwi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
The phenomenological method is being used in this qualitative research. Students at Universitas Negeri Manado used the TikTok program frequently while learning chemistry, according to data analysis employing paradigm interpretation. From the first to the third year, fifteen UNIMA Chemistry students participated in the study and served as informants to collect data. The research's primary and secondary data were gathered through in-person interviews and direct observation. The believability, transferability, dependability, and confirmability of the data were examined for quality. Data reduction, data display, and the process of drawing conclusions/verifying those conclusions were all steps in the processing of the data that Miles and Hubernan pioneered. Researchers came to the following conclusions based on their research: 1) Since the outbreak, TikTok has quickly surpassed YouTube, WhatsApp, and Zoom Meeting in terms of usage, becoming the most popular app; 2) TikTok content, which was previously only for entertainment, has migrated to learning media, including chemistry learning; 3) chemistry content in the form of videos based on experiments or practicums is able to hold students' attention; and 5) the TikTok application can be used as a media alternative in learning that is suitable for Gen Z students.